The combined modelling of dynamic systems control - Alzbutas, Robertas; Janilionis, Vytautas (Lietuvos matematikos rinkinys, 1999)
The advantages and disatvantages of modelling methods were evaluated, afterwards the combined modelling was proposed and the corresponding software was developed. This software allows formalization and modelling of different parts of the same system using different aggregate and dynamic mathematical modelling schemes (A-scheme and D-scheme). The usage and application of the developed combined modelling means are presented.